Inadvertent Intra-arterial Dialysis Catheter Insertion Into Common Carotid Artery With Successful Endovascular Kissing Stent Insertion - Mohammad Kazmin, NE; Mustafar, R; Wan Daud, WR; Mohd, R; Kamaruzaman, L; Fong, VK; Zainal, IA; Nik Ismail, NA; Haron, H; Abdul Razak, NZ; Abdul Gafor, AH (International Society of Nephrology, 2024)
Non-Indexed Publication